Students' Computational Thinking Process in Solving PISA Problems of Change and Relationship Content Reviewed from Students’ Self Efficacy - Ananda Jullailatul Azizia; Imam Kusmaryono; Hevy Risqi Maharani; Ahmad Arifuddin (EduMa: Mathematics education learning and teaching, 2023)
This research focuses on the stages of students' computational thinking processes in solving PISA questions about change and relationship content in terms of self-efficacy. The subjects of this study were 15-year-old students of class X MIPA 3 MAN 1 Semarang City, totaling 22 students and selected 2 students who had high self-efficacy, 2 students who had moderate self-efficacy and 2 students who had low self-efficacy. This research method uses a qualitative descriptive approach. Data collection using questionnaires, test instruments and interviews. Data analysis in this study included data collection, data reduction presented in text form and drawing conclusions or verification. The results of the study show that students' computational thinking processes in solving PISA questions about change and relationship content that have high self-efficacy can reach the stages of decomposition, pattern recognition, abstraction and algorithmic thinking as well as students' thought processes in carrying out plans can link real problems into mathematical problems. Whereas students who have self-efficacy are reaching the stages of decomposition, pattern recognition, abstraction and algorithmic thinking and in carrying out plans do not connect real problems to mathematical problems but use logic. Whereas students who have low self-efficacy only reach the stages of decomposition and pattern recognition have not done abstraction and algorithmic thinking because students' thinking processes in carrying out plans use logic and in solving these problems do not provide conclusions of answers and logical steps